URGENSI PENYERAGAMAN POLA KOMUNIKASI ACCOUNT REPRESENTATIVE DAN PERANNYA DALAM PENINGKATAN EFEKTIVITAS PENGAWASAN KEPATUHAN PAJAK - Mas Eko Affandi (Scientax, 2021)
The low level of completion of SP2DK, which has an important function in fostering and monitoring taxpayers as a mechanism to increase voluntary taxpayer compliance become the reason for this paper. The low completion of SP2DK during the pandemic is thought to have arisen not only because the economic downturn but also due to ineffective communication problems in counseling activities. Using a qualitative research method with a phenomenological approach, the study utilizes several secondary data such as education level, psychology test results, and also primary data from survey results and in-depth interviews with Account Representatives. Research seeks to identify communication problems that arise from counseling activities. The results of research that found problems related to Account Representative communication competence suggest the urgency of uniforming communication patterns in counseling activities as an effective communication guide as well as mechanism to leverage Account Representative communication competence.